Laryngeal Markedness in Chhatthare Limbu: An Optimality Theoretic Analysis - Chaursiya, Krishan (Journal of Productive Discourse, 2023)
This paper looks at the laryngeal contrast in Chhatthare Limbu and formalises the phonological effects through an optimality theoretic analysis. It discusses the underlying laryngeal feature specification in the language and how it fares with the constraint ranking in the language. The analysis shows that while the voicing and aspiration contrasts are available in the language, the context sensitive markedness and faithfulness constraints inhibit the free occurrence of these contrasts.